3D natural convection in a cubical cavity with a thermally active heater under the presence of an external magnetic field. (10th April 2016) - Purusothaman, A.; Oztop, H.F.; Nithyadevi, N.; Abu-Hamdeh, Nidal H.
Highlights: Study of the 3D natural convection heat transfer and flow characteristics is described under the presence of magnetic field. Benchmarking results for validating numerical models. Remarkable modification of the flow structure exists when the direction of magnetic field changes. Heat transfer rate and flow characteristics strongly depend upon the strength of the magnetic field. Abstract: A numerical study of three dimensional natural convection heat transfer and fluid flow in a cubical cavity induced by a thermally active plate is described under the presence of external magnetic field. The active plate is attached to the center of one vertical wall of the cavity filled with different fluids as mercury, air and dielectric liquid FC-77. It is located at two different positions as vertical or horizontal. The governing equations are solved by using finite volume method. Computations are performed for a wide range of Hartmann number (0 ≤ Ha ≤ 300), Prandtl number (0.025 ≤ Pr ≤ 25) and different aspect ratio of the plate ( Ac = 0.5 & 1.0) when the Rayleigh number Ra is fixed to be 10 7 . It is found that the heat transfer rate is strongly suppressed by the X and Y directional magnetic fields and it is weakly suppressed by the Z directional magnetic field.